Field results of a navigation architecture with timing constraints - Silva, Jorge (2015)
This paper presents results of field tests of a mobile robot controlled by a navigation architecture accounting for timing constraints in an indoor environment. Dependability properties characterize the effects of disturbances on the ability to successfully accomplish any assigned missions, described in terms of the stability of an equilibrium state identified with a goal location. The stability is analyzed using Contraction theory. A localization system based on artificial landmarks is used to obtain location estimates that enable the robot to autonomously cover large distances. Monte Carlo tests assess the architecture under different real environment conditions including recovering from disturbing events such as landmark detection failures, robot kidnapping, unexpected collisions, and changes in the density of obstacles in the environment. Tests include long-run missions of around 2900m lasting for 4.5 hours.